2014
DOI: 10.1128/iai.02323-14
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Oligopeptide Permeases Modulate Sporulation Initiation in Clostridium difficile

Abstract: The anaerobic gastrointestinal pathogen Clostridium difficile must form a metabolically dormant spore to survive in oxygenic environments and be transmitted from host to host. The regulatory factors by which C. difficile initiates and controls the early stages of sporulation in C. difficile are not highly conserved in other Clostridium or Bacillus species. Here, we investigated the role of two conserved oligopeptide permeases, Opp and App, in the regulation of sporulation in C. difficile. These permeases are k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
165
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(170 citation statements)
references
References 100 publications
4
165
0
1
Order By: Relevance
“…Isolates D and E1 also shared an SNV in the oligotransport-ATP binding domain of oppF (Table 4), which belongs to an operon of oligopeptide permease (opp) genes that are involved in regulating sporulation (among other processes) in some species of Bacillus and Clostridium (18,19). In vitro sporulation studies on all isolates revealed no significant difference (data not shown) in the rate of sporulation between isolate D and E1 and all other isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolates D and E1 also shared an SNV in the oligotransport-ATP binding domain of oppF (Table 4), which belongs to an operon of oligopeptide permease (opp) genes that are involved in regulating sporulation (among other processes) in some species of Bacillus and Clostridium (18,19). In vitro sporulation studies on all isolates revealed no significant difference (data not shown) in the rate of sporulation between isolate D and E1 and all other isolates.…”
Section: Discussionmentioning
confidence: 99%
“…However, these data may not be representative of in vivo sporulation characteristics; therefore, it cannot be conclusively proven that this SNV had no effect. The opp operon is involved in other processes in other organisms, for example, competence in Bacillus and Streptococcus species, plasmid transfer in Enterococcus faecalis, and the expression of virulence factors in Bacillus thuringiensis (18,20). Therefore, SNVs in this region may have a yetundiscovered role in C. difficile virulence and could present a further avenue of research.…”
Section: Discussionmentioning
confidence: 99%
“…It is speculated that oligopeptides taken up as nutrients are responsible for this inverse regulation of virulence of C. difficile. 55 In case of the facultative intracellular pathogen Listeria monocytogenes, the gene oppA is required for survival inside macrophages besides providing nutrition. 56 …”
Section: Gram Positive Pathogensmentioning
confidence: 99%
“…In previous work, we found that the two oligopeptide transporters Opp and App inhibit the initiation of sporulation in C. difficile (19). It was proposed that Opp and App inhibit sporulation by importing peptides into the cell.…”
mentioning
confidence: 99%
“…All cultures were anaerobically incubated at 37°C while being monitored for growth and spore production. Micrographs were taken and enumerated as previously described (19), with minor modifications. Approximately 24 h following the start of stationary phase (T 24 ), 1-ml samples were taken from the cultures.…”
mentioning
confidence: 99%